The association between serum microbial DNA composition and symptoms of depression and anxiety in mood disorders - Sang Jin Rhee; Hyeyoung Kim; Yunna Lee; Hyun Jeong Lee; C. Hyung Keun Park; Jinho Yang; Yoon-Keun Kim; Yong Min Ahn (Scientific Reports, 2021)
Abstract There is increasing evidence supporting the association between gut microbiome composition and mood disorders; however, studies on the circulating microbiome are scarce. This study aimed to analyze the association of the serum microbial DNA composition with depressive and anxiety symptoms in patients with mood disorders. The sera of 69 patients with mood disorders, aged from 19 to 60, were analyzed. Bacterial DNA was isolated from extracellular membrane vesicles and, subsequently, amplified and quantified with specific primers for the V3–V4 hypervariable region of the 16S rDNA gene. Sequence reads were clustered into Operational Taxonomic Units and classified using the SILVA database. There were no significant associations between alpha diversity measures and the total Hamilton depression rating scale (HAM-D) or Beck anxiety inventory (BAI) scores. Only the weighted UniFrac distance was associated with the total HAM-D score (F = 1.57, p = 0.045). The Bacteroidaceae family and Bacteroides genus were negatively associated with the total HAM-D score (β =  − 0.016, p < 0.001, q = 0.08 and β =  − 0.016, p < 0.001, q = 0.15, respectively). The Desulfovibrionaceae family and Clostridiales Family XIII were positively associated with the total BAI score (β = 1.8 × 10−3, p < 0.001, q = 0.04 and β = 1.3 × 10−3, p < 0.001, q = 0.24, respectively). Further studies with larger sample sizes and longitudinal designs are warranted.